Genomic Approach to Identification of Mutations Affecting Caspofungin Susceptibility in Saccharomyces cerevisiae - Markovich, Sarit (Antimicrob Agents Chemother, 2004)
The antifungal agent caspofungin (CAS) specifically interferes with glucan synthesis and cell wall formation. To further study the cellular processes affected by CAS, we analyzed a Saccharomyces cerevisiae mutant collection (4,787 individual knockout mutations) to identify new genes affecting susceptibility to the drug. This collection was screened for increased CAS sensitivity (CAS-IS) or increased CAS resistance (CAS-IR). MICs were determined by the broth microdilution method. Disruption of 20 genes led to CAS-IS (four- to eightfold reductions in the MIC). Eleven of the 20 genes are involved in cell wall and membrane function, notably in the protein kinase C (PKC) integrity pathway (MID2, FKS1, SMI1, and BCK1), chitin and mannan biosynthesis (CHS3, CHS4, CHS7, and MNN10), and ergosterol biosynthesis (ERG5 and ERG6). Four of the 20 genes (TPO1, VPS65, VPS25, and CHC1) are involved in vacuole and transport functions, 3 of the 20 genes (CCR4, POP2, and NPL3) are involved in the control of transcription, and 2 of the 20 genes are of unknown function. Disruption of nine additional genes led to CAS-IR (a fourfold increase of MIC). Five of these nine genes (SLG1, ERG3, VRP1, CSG2, and CKA2) are involved in cell wall function and signal transduction, and two of the nine genes (VPS67 and SAC2) are involved in vacuole function. To assess the specificity of susceptibility to CAS, the MICs of amphotericin B, fluconazole, flucytosine, and calcofluor for the strains were tested. Seven of 20 CAS-IS strains (with disruption of FKS1, SMI1, BCK1, CHS4, ERG5, TPO1, and ILM1) and 1 of 9 CAS-IR strains (with disruption of SLG1) demonstrated selective susceptibility to CAS. To further explore the importance of PKC in CAS susceptibility, the activity of the PKC inhibitor staurosporine in combination with CAS was tested against eight Aspergillus clinical isolates by the microdilution assay. Synergistic or synergistic-to-additive activities were found against all eight isolates by use of both MIC and minimum effective concentration endpoints.